The IFS Green Budget: October 2019 - Ben Zaranko; Christine Farquharson; Paul Johnson (Institute for Fiscal Studies (IFS), 2019)
The IFS Green Budget 2019, in association with Citi and the Nuffield Foundation, is edited by Carl Emmerson, Christine Farquharson and Paul Johnson, and copy-edited by Judith Payne. The report looks at the issues and challenges facing Chancellor Sajid Javid as he prepares for his first Budget.
Keywords: 330; Öffentlicher Haushalt; Finanzpolitik; Steuerpolitik; Großbritannien